2006
DOI: 10.1016/j.jasms.2006.03.006
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic range of mass accuracy in LTQ orbitrap hybrid mass spectrometer

Abstract: Using a novel orbitrap mass spectrometer, the authors investigate the dynamic range over which accurate masses can be determined (extent of mass accuracy) for short duration experiments typical for LC/MS. A linear ion trap is used to selectively fill an intermediate ion storage device (C-trap) with ions of interest, following which the ensemble of ions is injected into an orbitrap mass analyzer and analyzed using image current detection and fast Fourier transformation. Using this technique, it is possible to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
307
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(330 citation statements)
references
References 16 publications
11
307
0
4
Order By: Relevance
“…spread of measured m/z below 3 ppm and it drops to 1-1.7 ppm for S/N Ͼ 7 (systematic shift of 2 ppm is just the result of external calibration). This fits with observations from [13]. These data prove that the full noise band of a standard Orbitrap preamplifier for a 0.76 s acquisition is equivalent to about five to six elementary charges, whilst the full noise band for a 1.5 s acquisition is equivalent to about four elementary charges!…”
Section: Resultssupporting
confidence: 86%
“…spread of measured m/z below 3 ppm and it drops to 1-1.7 ppm for S/N Ͼ 7 (systematic shift of 2 ppm is just the result of external calibration). This fits with observations from [13]. These data prove that the full noise band of a standard Orbitrap preamplifier for a 0.76 s acquisition is equivalent to about five to six elementary charges, whilst the full noise band for a 1.5 s acquisition is equivalent to about four elementary charges!…”
Section: Resultssupporting
confidence: 86%
“…A recent study [12] demonstrated that an Orbitrap mass resolving power of 25,000 to 40,000 was essential to obtain sufficient selectivity to enable the detection and quantification of N-nitrosamines in drink-N N ing water and wastewater samples at low ng/L level. The larger dynamic range over which accurate masses can be determined of LTQ Orbitrap MS could be a distinct advantage over TOFMS [13].…”
mentioning
confidence: 99%
“…It has many parallels with the LIT/FT-ICR, substituting the orbitrap mass analyzer for the FT-ICR spectrometer [82]. A schematic [83] of the LIT/orbitrap is shown in Figure 6. This design has some analogies to the beam-beam instruments (e.g., Q/TOF) in that the ions are transferred from one analyzer to another, but rather than being a continuous stream, the ions are moved in packets after they have been accumu- lated in the LIT.…”
Section: Trap-beam Hybrid Instrumentsmentioning
confidence: 99%